Viabilidade econômico-financeira da migração do ambiente de contratação regulado para o ambiente de contratação livre: Base Aérea de Santa Maria, um estudo de caso - Antunes, Fabio Lunardi (2023)
The purpose of this project is to develop an analysis methodology that allows to evaluate the economic-financial viability of migration from the Santa Maria Air Base (BASM) from the Regulated Contracting Environment (ACR) to the Free Contracting Environment (ACL). The efficiency principle, which seeks to do more with less, is one of the principles of public administration. Therefore, this principle can be applied in the search for reduction of electricity costs without harming the organization's operability. BASM constantly seeks to reduce its electricity consumption by improving its facilities and processes, such as participating in public calls for Energy Efficiency Projects (PEE) and using renewable energy sources in its plant. The unit is aligned with Environmental, Social and Governance (ESG) practices, such as solid waste management, Sustainable Logistics Plan (PLS), effluent management and treatment, sustainable procurement in the acquisition of goods and engineering works, use of digital signatures to reduce paper processes, and social actions with the local community. This way, migrating to the ACL, BASM could further expand its ESG implementation actions. To identify the key elements in the analysis of the migration feasibility to the ACL, a quantitative survey of the organization's electricity bills is proposed in order to process the profile and historical consumption of the consumer unit, so that cost simulations can be carried out for adjustments in contracted demands and comparisons between the current situation in the captive market and energy contracts from conventional and incentivized sources in the free market. The results are positive and demonstrate that the migration from the regulated to the free contracting environment results in a reduction of electricity costs at BASM, with at least a 16.96% reduction in long-term contracts compared to the ACR, as shown by the case studies.